PENGABDIAN UNTUK MENINGKATKAN DAYA SAING DENGAN MENGIMPLEMENTASIKAN EKONOMI DIGITAL PADA UMKM USAHA KERIPIK PISANG DIMAS - Kusuma, Surya (P3M STIE Pembangunan Tanjungpinang, 2024)
This service aims to develop digital literacy-based MSMEs for Kawal Kelurahan business actors, Bintan Regency. One of the SMEs in the Kawal sub-district is the Dimas Banana Chips UMKM. The methods in this service are surveys, training and direct assistance in the field with the aim of MSME owners having new knowledge about digitizing MSMEs that every MSMEs should have done and used this digital literacy, which can be obtained at low cost and free of charge